Understanding OECD representations of teachers and teaching: a visual discourse analysis of covers in OECD documents. (15th March 2019) - Berkovich, Izhak; Benoliel, Pascale
ABSTRACT: OECD dominance in the international educational policy discourse in the developed regions of the world, particularly in promoting teaching policy, has been long acknowledged. While many works have explored the organisation's verbal discourse, no study has considered exploring its visual discourse. To close that gap, we employed a visual discourse analysis on the covers of OECD documents pertaining to teachers and teaching (i.e., TALIS and ISTP). The analysis found that OECD's covers drew on two discourses, a conservative discourse and a liberal diversity discourse. However, the latter was entangled with constructions which serve to maintain a conservative order.